Analysis of Intestinal Microflora and Metabolites From Mice With DSS-Induced IBD Treated With Schistosoma Soluble Egg Antigen - Zhu, Tianyu; Xue, Qingkai; Liu, Yiyun; Xu, Yongliang; Xiong, Chunrong; Lu, Jin; Yang, Haitao; Zhang, Quan; Huang, Yuzheng (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to analyze the changes in intestinal flora and metabolites in the intestinal contents of mice with IBD to preliminarily clarify the mechanism of action of SEA on IBD, thus, laying a research foundation for the subsequent treatment of IBD. A total of 40 ICR mice were divided into 4 groups: control, SEA 50 μg, dextran sulfate sodium salt (DSS), and SEA 50 μg + DSS. The overall state of the animals was observed continuously during modeling. The colonic length was measured after 10 days of modeling. The degree of colonic inflammation was observed by hematoxylin and eosin staining. 16srRNA and liquid chromatography–mass spectrometry sequencing techniques were used to determine the abundance of bacteria and metabolites in the intestinal contents of mice in the DSS and SEA 50 μg + DSS groups, and the differences were further analyzed. Results: After SEA intervention, the disease activity index score of mice with IBD decreased and the colon shortening was reduced. Microscopically, the lymphocyte aggregation, glandular atrophy, goblet cell disappearance, and colonic inflammation were less in the SEA 50 μg + DSS group than in the DSS group (P < 0.0001). After SEA intervention, the abundance of beneficial bacteria prevotellaceAE_UCG-001 was upregulated, while the abundance of the harmful bacteria Helicobacter, Lachnoclostridium, and Enterococcus was downregulated in the intestinal tract of mice with IBD. The intestinal metabolite analysis showed that SEA intervention decreased the intestinal contents of glycerophospholipids (lysophosphatidylcholine, lysophosphatidylethanolamine, phatidylcholine, and phatidylethanolamine) and carboxylic acids (L-alloisoleucine and L-glutamate), whereas increased bile acids and their derivatives (3B,7A,12a-trihydroxy-5A-cholanoic acid and 3A,4B,12a-trihydroxy-5b-cholanoic acid). Combined microbiota–metabolite analysis revealed a correlation between these differential microbiota and differential metabolites. At the same time, the changes in the contents of metabolites and differential metabolites in the two groups also correlated with the abundance of the gut microbiome. The study showed that SEA reduced DSS-induced inflammation in IBD and improved the symptoms of IBD in mice through the combined regulation of intestinal flora and intestinal metabolism. It suggested a potential possibility for the use of SEA in treating and regulating intestinal flora and metabolism in patients with IBD.